(untitled) (Islamic Sciences Journal, 2025)
This study aimed to investigate the narrations of the successor (tabi’i) Amr bin Maymun Al-Awdi in the book Sunan Abi Dawood, through a comprehensive critical hadith analysis that included sourcing the narrations, verifying the chains of transmission, and identifying the subtle isnad nuances and derived benefits. Six of his hadiths were analyzed, five of which were found to be authentic (sahih) and one was hasan in the studied sample. The results showed that his narrations were predominantly authentic, his chains were sound, and his transmitters demonstrated strong accuracy, with minor verbal variations that did not affect meaning or ruling. The study confirms the standing of Amr ibn Maymun al-Awdi among the tabi‘in, the confidence hadith scholars place in his narrations, and the importance of giving his narrations attention in service of the Prophetic Sunnah.